Consumption of psychoactive substances and the relation with vulnerability and poverty in Argentina - Abeldaño, Roberto Ariel; Fernández, Alicia Ruth; Estario, Juan Carlos; Ventura, Carla Aparecida Arena (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2014)
A total of 6,122 cases taken from the National Survey of Psychoactive Substance Prevalence - Encuesta Nacional de Prevalencia de Consumo de Sustancias Psicoactivas (ENPreCoSP-2.008) were analyzed in order to determine the prevalence of consumption of legal and illegal psychoactive substances in the 18-34 year old population group in 10 Argentinian provinces and the relationship with Unsatisfied Basic Needs and level of income. Consumption was more prevalent among males and those aged 18-24. Logistic regression of consumption of legal substances in the preceding month showed that Unsatisfied Basic Needs and being male to be risk factors, whereas income above the poverty line was a protection factor (p<0,05).